2008
DOI: 10.1007/s10531-008-9320-9
|View full text |Cite
|
Sign up to set email alerts
|

Conservation planning in a subdivided world

Abstract: The identiWcation of priority areas for conservation tends to take place over two fundamentally diVerent spatial extents. First, there are analyses conducted at global or large biogeographic extents. Second, there are those conducted within geopolitical units. In this paper we show, using data for North American mammals, that spatial extent can have a profound eVect both on the number and locations of the priority areas identiWed to attain a particular conservation goal. For example, applying the same selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…Thus, if conservation planners wish to protect vegetation types across different portions of their range to include varying patterns within the vegetation types, greater total area will be needed. Similar effects of scale in conservation planning have been observed by other authors (Erasmus et al 1999;Vazquez, Rodriguez, and Arita 2008), whose studies found an even greater scale effect (up to an order of magnitude) on conservation targets than was identified in this study. This study, however, shows the effects not just of the number of subunits but of boundary locations as well.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, if conservation planners wish to protect vegetation types across different portions of their range to include varying patterns within the vegetation types, greater total area will be needed. Similar effects of scale in conservation planning have been observed by other authors (Erasmus et al 1999;Vazquez, Rodriguez, and Arita 2008), whose studies found an even greater scale effect (up to an order of magnitude) on conservation targets than was identified in this study. This study, however, shows the effects not just of the number of subunits but of boundary locations as well.…”
Section: Discussionsupporting
confidence: 92%
“…While several studies have shown that spatial extent can affect conservation plans (7)(8)(9)(10), little is known about the increased effectiveness of coordinated conservation plans across numerous countries. As far as we are aware, most of the previous studies have examined the effect over 2 countries at the most (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…As far as we are aware, most of the previous studies have examined the effect over 2 countries at the most (7)(8)(9)(10). Regional coordination can be especially important in places where a single biome is split between several geopolitical units that vary not only in their levels of biodiversity, but also in their conservation threats and the cost of conservation action.…”
mentioning
confidence: 99%
“…In order to avoid conflicts in outcomes of conservation planning exercises at different geographical scales (Vazquez et al 2008), targets should be proportionally assigned to the planning region. For example, if 10% of the range/distribution of a species occurs within the planning region, the proportional target would be at least one location (or population or locality) and 1,000 mature individuals.…”
Section: Methodsmentioning
confidence: 99%
“…It is debatable whether this goal is achieved by the current approaches to setting species targets for conservation planning purposes, which range from simple approaches of representing each species at least once (Loyola et al 2009) to multiple representation targets (Vazquez et al 2008) where the number of sites to represent a species are often decided arbitrarily, and to percentage targets involving arbitrarily selected proportions or percentages of the distribution areas of species (Rondinini et al 2005;Meynard et al 2009;Sarkar et al 2009). A more complex method of setting targets for species has been devised by Burgman et al (2001), but the method is data intensive requiring knowledge of demographic and environmental uncertainties, disturbance regimes, deterministic trends causing permanent habitat loss and catastrophes.…”
Section: Vu Vulnerable Nt Near Threatened Lc Least Concernmentioning
confidence: 99%